Public relations : strategies and tactics - Wilcox, Dennis L. (Boston, Massachusetts : Pearson Education Asia Pte. Ltd., 2015)
This new edition is consistent in offering a comprehensive overview of today's public relations practice on the local, national and international level. The suggestions of adopters and reviewers regarding the 10th edition have been given serious consideration and have helped make this edition even better than the last one.
Part 1. role -- Part 2. Process -- Part 3. strategy -- Part 4. Tactics -- Part 5. Application .
Includes bibliographical references and index.
Keywords: PUBLIC RELATIONS